Standing in awe of scientific healthcare - Oberholzer, Annemarie E. (HTS teologiese studies, 2019)
Spirituality and healthcare have been dependant on and supported one another from the earliest times. However, this marriage eventually found itself in stormy waters and parted ways, blaming scientific advances in healthcare for the split. But, as in any broken marriage, the story usually has two sides, and the blame for this split cannot be put squarely on science. In fact, scientific research is now trying to bridge the gap, whereas in the field of Christian spirituality, some are even opposing medical practices and the use of medicine as it could portray a belief in the science of healthcare, as opposed to God. These beliefs only serve to widen the gap between spirituality and healthcare, alienating Christianity from healthcare. If we want to restore the marriage between spirituality and healthcare, it is important to reflect on these beliefs.The purpose of this article is therefore to explore and critically reflect on the relationship between spirituality and healthcare from a Christian perspective. The objective is to identify and address beliefs that are alienating Christianity from healthcare, arguing that, rather than opposing medical practices, we could stand in awe of scientific healthcare.